PENGARUH KOMITE AUDIT, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Alit Dwi Maha Dewi, Ida Ayu; Wirawati, Ni Gusti Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024, 2024)
Firm value is one of the factors considered for investing by investors. Firm value is a reflection of society’s assessment of company performance which is reflected by the share price that is formed form the demand and supply of the capital market. This study aims to examine the influence of the audit committee, leverage and firm size on firm value. This research was conducted at consumer goods manufacturing companies listed on the Indonesia Stock Exchange for the 2019 -2021 period. Determination of the sample on this study using purposive sampling method. Based on this method, the number of samples used is 48 samples. The data of this study were analyzed using multiple linear regression analysis techniques. The results of this study indicate that firm size has a positive effect on firm value while the audit committee and leverage have no effect on firm value. The implications of this research can be prove the agency theory which explains the variable company size where the larger the size of the company, the movement of of the company’s value will increase good.